Photogalvanic Cell for Solar Energy Conversion: Eosin-Glucose System - Khandelwal, R.C.; Singh, Sadhana (Asian Journal of Chemistry, 2010)
A photogalvanic cell containing eosin as the photosensitizer and glucose as the reductant has been used for solar energy conversion. The photopotential and photocurrent generated by this cell were 412 mV and 16.0 μA respectively. The effects of various parameters like pH, reductant and dye concentration, light intensity, temperature etc. on the electrical output of the cell have been studied. The current-voltage (i-V) characteristics of the cell have also been observed. A tentative mechanism for the generation of the photocurrent in this photogalvanic cell has been proposed.